Analysis of Hypo- and Hyperphosphatemia in an Intensive Care Unit Cohort. (June 2017) - Broman, Marcus; Wilsson, Amanda M. J.; Hansson, Fredrik; Klarin, Bengt
Abstract : BACKGROUND: Blood phosphate levels are vulnerable to fluctuations and changes in phosphate levels are often neglected. The aim of this study was to evaluate whether deviations in phosphate levels correlate to higher 180-day overall mortality or morbidity. METHODS: Four thousand six hundred fifty-six patients with 19, 467 phosphate values treated at the adult intensive care unit at Skåne University Hospital, Lund, Sweden during 2006–2014 were retrospectively divided into a control group and 3 study groups: hypophosphatemia, hyperphosphatemia, and a mixed group showing both hypo/hyperphosphatemia. Sex, age, disease severity represented by maximal organ system Sequential Organ Failure Assessment score, renal Sequential Organ Failure Assessment score, lowest ionized calcium value, and diagnoses classes were included in a Cox hazard model to adjust for confounding factors, with time to death in the first 180 days from the intensive care unit (ICU) admission as outcome. RESULTS: When compared to normophosphatemic controls, the hyperphosphatemic study group was associated with higher risk of death with a hazard ratio of 1.2 (98.3% confidence interval 1.0–1.5, P = .0089). Mortality in the hypophosphatemic or mixed study group did not differ from controls. The mixed group showed markedly longer ventilator times and ICU stays compared to all other groups. CONCLUSIONS: Phosphate alterations in ICU patients are common and associated with worse morbidity and mortality. Many underlying pathophysiologic mechanisms may play a role. A rapidly changing phosphate level or isolated hypo or hyperphosphatemia should be urgently corrected.